2017
DOI: 10.1177/0883073817702782
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Patient Perceptions of Functional Impairment Due to Tourette Syndrome: Development of a Shortened Version of the Child Tourette Syndrome Impairment Scale

Abstract: The Child Tourette Syndrome Impairment Scale (CTIM) rates 37 problems in school, social, and home domains separately for tics and for comorbid diagnoses. However, a shorter version would be easier to implement in busy clinics. Using published data from 85 children with Tourette syndrome, 92 controls, and parents, factor analysis was used to generate a "mini-CTIM" composed of 12 items applied to tic and comorbid diagnoses. Child- and parent-rated mini-CTIM scores were compared and correlated across raters and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…This intake paperwork contained history of present illness/interval history, routine pertinent clinical information, current medications and psychiatric/psychological care, and the following rating scales: A parent report tic-severity scale based on the Yale Global Tic Severity Scale (YGTSS) 19 (Online Appendix 1), the Attention-Deficit Hyperactivity Disorder Rating Scale (ADHD RS), 20 a “mini-CY-BOCS” shortened version of the CY-BOCS 21 (Online Appendix 2), and the mini-CTIM. 14,18 The mini-CTIM (Online Appendix 3) is a 14-item questionnaire that asks children and their parents to rate the child’s impairment in school, home, and social domains due to tics separately from difficulty with these activities due to comorbid ADHD, OCD, anxiety, rages, or other. Children and parents select “not at all” (0), “just a little” (1), “pretty much” (2), or “very much” (3) for each activity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This intake paperwork contained history of present illness/interval history, routine pertinent clinical information, current medications and psychiatric/psychological care, and the following rating scales: A parent report tic-severity scale based on the Yale Global Tic Severity Scale (YGTSS) 19 (Online Appendix 1), the Attention-Deficit Hyperactivity Disorder Rating Scale (ADHD RS), 20 a “mini-CY-BOCS” shortened version of the CY-BOCS 21 (Online Appendix 2), and the mini-CTIM. 14,18 The mini-CTIM (Online Appendix 3) is a 14-item questionnaire that asks children and their parents to rate the child’s impairment in school, home, and social domains due to tics separately from difficulty with these activities due to comorbid ADHD, OCD, anxiety, rages, or other. Children and parents select “not at all” (0), “just a little” (1), “pretty much” (2), or “very much” (3) for each activity.…”
Section: Methodsmentioning
confidence: 99%
“…17 We then performed a factor analysis to create a shortened questionnaire with a goal to decrease response burden. 18 This shortened version, the mini-Child Tourette Syndrome Impairment Scale (mini-CTIM), correlated strongly with the original scale and maintained association of worsened non-tic impairment scores in the presence of comorbidities. 18 Importantly, however, these 2 publications did not include concurrent ratings of ADHD or OCD symptom severity using standardized rating scales.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…developed a Mini‐CTIM comprising only 12 items related to school, home, and social activities with the aim of evaluating parent‐child results, group differences, and symptom severity corrections. The authors found that this concise scale is a practical tool for assessing both tic‐ and non‐tic‐based impairments . The widely used 14‐item Parent Tic Questionnaire (PTQ) evaluates motor and vocal tics and provides information about both frequency (1: weekly, 2: daily, 3: hourly, 4: constantly) and intensity .…”
Section: Behavioral Assessments Of Pmdsmentioning
confidence: 99%
“…The authors found that this concise scale is a practical tool for assessing both tic-and non-tic-based impairments. 46 The widely used 14-item Parent Tic Questionnaire (PTQ) evaluates motor and vocal tics and provides information about both frequency (1: weekly, 2: daily, 3: hourly, 4: constantly) and intensity. 47 The PTQ was found to validly and reliably assess tic severity.…”
Section: Ticsmentioning
confidence: 99%